Aplikasi Marketplace Penyewaan Lapangan Olahraga Dari Berbagai Cabang Dengan Metode Agile Development - Kharis Anwar; Lilik Dwi Kurniawan; M. Ijur Rahman; Nur Ani (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Competition in sports field leasing is quite fast these days, making sports field managers improve facilities and provide competitive prices to attract sports field tenants. However, this progress was not accompanied by advances in technology so that sports field managers still had to do the manual method for field operations and promotion. On the side of the tenants of the sports field also still have to go to the sports field to find out the availability of schedules, facilities, and prices offered. Then many tenants who have an interest in exercising more than one branch of sport, therefore researchers use the concept of a marketplace that can bring together the managers of sports fields with field tenants in one container. In the application development process, it is done by using the agile method application development method because in its development it can be possible to collaborate and correct each other among team members to increase the customer satisfaction ratio. The application implementation uses the Laravel framework, PHP for programming language, and the MySQL for Database Management System. The results of the study can be concluded that the use of the marketplace concept can bring together prospective field tenants with many field managers and the ease of finding a sports field following the wishes of tenants by selecting the category of field, price and closest location and the manager of the sports field can promote the sports field by registering the field.